7 - Regards croisés sur la crise africaine: by Boubacar Barry - Boubacar Barry (Africa Development, 1994)
In order for Africa to solve the crisis it is facing, it is important that African researchers know Africa better by analysing the various steps of its history both sequentially and in the long run and taking into account the various aspects of the major groupings such as the Senegambia, Benin Gulf and Niger loop. Such research activities are all the more urgent owing to the fact that since the nineteenth centwy, neither colonial rule nor the structural adjustment programs now being implemented have paved the way to development.